PENGARUH PENERAPAN MODEL PEMBELAJARAN ACTIVE LEARNING TIPE QUIZ TEAM TERHADAP KEMAMPUAN BERPIKIR KRITIS DENGAN VARIABEL MODERATOR MOTIVASI BELAJAR PESERTA DIDIK - Poy Saefullah Zevender (Sinau : Jurnal Ilmu Pendidikan dan Humaniora, 2019)
This research was motivated by observations and interviews stating that the critical thinking skills by taking into account the motivation of learners is still low. The purpose of this study was to determine whether there is influence from learning model Active Learning Type Quiz Team about the critical thinking skills of learners, whether there is influence learning motivation of students towards critical thinking skills of learners, and whether there is an interaction effect between teaching model active learning type of quiz team to learning motivation towards critical thinking skills of learners. The method used is experimental method with factorial design. This caused the hypothesis testing is done by using two way analisys of variance in order to avoid noise or a possibility that states there is an effect due to mixing of the data analysis. Meanwhile, the population in this study were all students of class X as many as 309 students and the sample is class X-2 as the experimental class and X-3 as the control class, each of which consists of 39 students. Based on the results of the study showed: There is the influence of learning model Active Learning type Quiz Team of the critical thinking skills of learners with sig. 0.000 <0.05. There is the influence of learning motivation towards the critical thinking skills of learners with sig. 0.003 <0.05. There is an interaction effect between the active learning teaching model type quiz team with the learning motivation towards the critical thinking skills of learners with sig. 0.000 <0.05. To reach the maximum critical thinking skills, it is recommended that the teachers continue to practice, formulate and present problems that exist into the learning process as a stimulus for students to get them used to find the solution of a problem that occurs in daily life.